Membangun Ketahanan (Resiliensi) Pada Mahasiswa Ketika Kuliah Di Masa Pandemi - Supadi Supadi; Widjijati Widjijati; Esti Dwi Widayanti (Prodi Keperawatan Purwokerto, 2021)
Background : Based on the joint decree of the ministry of education and culture, ministry of religion, ministry of health and ministry of home affairs number 01 / KB / 2020,516 year 2020, HK.03.01 / menkes / 363 / 2020,440-882 regarding learning guides in the school year and year In the new academic period during the pandemic corona virus disease (covid 19), it was stated that the health and safety of students, educators, staff, families and communities were the main priorities in determining learning policies (Joint Ministry Decree, 2020).Methods : This study used a cross-sectional observational analytic design, namely analyzing the relationship between resilience level (building body resistance) and stress levels in students in the 2020/2021 academic new academic year learning. The statistical analysis test used was descriptive test for univariate variables and Mann Whitney and Wilcoxon tests for bivariate variables.Result : There was a significant difference in student resilience after the Proggesive Muscle Relaxation (PMR) action between before and after giving PMR action with a value of p = 0.000, there was a significant difference in student stress after PMR action between before and after giving PMR action with a value of p = 0.000, and The mean of respondent resilience after PMR action was 72.39 and the respondent's stress was 24.61. The result of statistical analysis test was p = 0.000, which means that there is a significant relationship between student resilience and student stress.Conclusion : Resilience (building resilience) is very high affects the level of stress. The higher a person's resilience level, the lower one's stress level or a person's stress level will be lighter.